Eltsov P. A. Siberian Century / trans. from Engl. - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
The article presents the translation of a separate chapter from the book of the American anthropologist, historian and political scientist Peter Eltsov, «Long Telegram 2: Neo-Kennanite Approach to Russia», which caused a strong resonance in Russia. In his book, the author gives recommendations to the American establishment about the policy towards Russia, predicting its potential collapse due to internal factors, which are argued in the published text